Influence of Silicon Dioxide-Titanium Dioxide Antireflective Electrosprayed Coatings on Multicrystalline Silicon Cells - Rajasekar Rathanasamy; Gobinath Velu Kaliyannan; Santhosh Sivaraj; Abishek Saminathan; Bharathikannan Krishnan; Dhayananth Palanichamy; Md. Elias Uddin (Advances in Materials Science and Engineering, 2022)
This research work primarily focuses on enhancing the power conversion efficiency (PCE) of polycrystalline silicon solar cells by using a single-layer and a double-layered antireflection coating deposited through the electrospraying technique. The usage of titanium dioxide and silicon dioxide as antireflection coating materials has shown a significant increase in the optical and electrical properties of solar cells under open and controlled light sources. The sample with TiO2 as a base layer and SiO2 as the top layer (sample B-IV) exhibited a maximum PCE of 18.90% in direct sunlight and 21.19% in a neodymium setup with cell temperatures of 40°C and 52.1°C, respectively. Sample B-IV has also shown the lowest resistivity of 3.1 × 10−3 Ω·cm among the coated samples. Also, an increase of 11.6% light transmittance and a reduction of 9.6% light reflectance were exerted by sample B-IV. The results obtained from different analysis proves that TiO2/SiO2 was an appropriate antireflection coating material for enhancing the PCE of the polycrystalline silicon solar cell.